Neonatal Outcome of 100 Cases of Term Pregnancy Having Meconium Stained Liquor in a Tertiary Level Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background : Presence of meconium in amniotic fluid is potentially a serious sign of fetal compromise and associated with an increased perinatal mortality and morbidities.Meconium stained amniotic fluid is considered a harbinger of fetal compromise because of its direct correlation with fetal distress and increased likelihood of aspiration of meconium with resultant deleterious effects on the neonatal lung. The purpose of the study was to find the neonatal outcome of pregnancy associated with meconium staining amniotic fluid. Outcome variable were birth weight, Apgar score, admission in NICU, neonatal complications, neonatal mortality and morbidity.Materials and methods : The present prospective  observational study was conducted in the Department of Obstetrics and Gynaecology in Bangabandhu Sheikh Mujib Medical University, Dhaka and Dhaka Medical College Hospital. A total of 100 pregnant women admitted in the labour ward with meconium stained liquor were the study population.Results : Nearly three-quarter (72%) of the patients were between 20 – 30 years followed by 17.2% more than 30 years and 10.8% below 20 years old. Over half (52.2%) of the neonates needed resuscitation and 58.7% had to be admitted in ICU. More than 90% of the neonates had normal birth weight and only 9.7% were of low birth weight. Over half (51.1%) of the neonates developed meconium aspirate syndrome and 10.5% respiratory distress syndrome. Neonatal jaundice and neonatal sepsis were observed in 5.4%, 4.3% neonates respectively. Ten neonates (10.5%) died early in the neonatal life, while 1(1.1%) was still-born. low APGAR score (< 7) at 1 and 5 minutes of birth was found in 63.6% and 53% of the cases respectively with thick meconium stained amniotic fluid as opposed to 26.3% and 17.7% of the cases respectively having thin meconium stained amniotic fluid (p = 0.002 and p = 0.014 respectively). Thick meconium tend to be associated with meconium aspiration syndrome (p < 0.001). Neonates needing immediate resuscitation and admission in ICU was staggeringly higher in the former group than those in the latter group (p < 0.001). The incidence of perinatal death was significantly higher in patients with thick meconium stained fluid than that in patients with thin meconium (p = 0.029).Conclusion : The study concluded that meconium stained amniotic fluid is associated with low APGAR score, higher incidence of MAS, ICU admission and perinatal death and their severity depends on the concentration of meconium.JCMCTA 2022 ; 33 (1) : 15-20